Synchronous Pleural and Peritoneal Mesothelioma in a Dog and its Diagnosis - Saravanan, S; Ramprabhu, R; Kumar, V; Sundararajan, R C (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dogs and human beings often share the common environment, and dogs have been considered as models and useful ‘environmental sentinels’ for cancer risk in humans. Canine mesothelioma is rare in dogs with benign or malignant occurrence and generally reported as pleural or pericardial type. A male, Labrador Retriever dog of two years and six months old was presented with the complaint of distended ventral abdomen, respiratory distress, and exercise intolerance since 4 months. Thoracocenetesis and abdominocentesis revealed presence of serosanguinous fluid and cytological examination confirmed the mesothelioma in pleural and peritoneal cavity. Ultrasonogram of the abdomen revealed a hyper echoic nodular mass and echogenic serosanguinous exudate in the peritoneal cavity. Haemato-biochemical analysis revealed leukocytosis, lymphocytosis, hypoalbuminemia, hyperkalemia and hypernatremia. Thoracocenetesis and abdominocentesis were performed to reduce the respiratory distress along with parentral administration of drugs, however the case succumbed to the disease.